2017
DOI: 10.1163/15707563-00002536
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity as a local and regional-scale driver of primate assemblage structure in northernmost Brazilian Amazonia

Abstract: We performed line transect surveys in two fishbone human settlements (defined as clearings cut through forests in a fishbone pattern, extending along secondary roads from a main road) in different vegetation types, as well as in one protected area. A total of 410 sightings of eight primate species were recorded in the three study areas. The mean total primate abundance was 3.28 groups/10 km walked, and there were significant differences between areas with different plant physiognomies. The abundance of the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Covariates of forest structure and productivity, such as stratification, floristic diversity, and phenology have been proposed as determinants of mammalian abundance (Malcolm, 1995;Gentile and Fernandez, 1999;Grelle, 2003;Marshall et al, 2014;Luna et al, 2017). Gadelha et al (2017), studying a primate community in a habitat similar to that in the current study, found a significant association between mammalian abundance, and absolute dominance of trees, number of clearings, and vegetation height. No studies to date, however, had tested the effects of the forest structure and productivity covariates on whole assemblages of medium-and large-sized mammals in totally protected areas in the Brazilian Amazonia.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Covariates of forest structure and productivity, such as stratification, floristic diversity, and phenology have been proposed as determinants of mammalian abundance (Malcolm, 1995;Gentile and Fernandez, 1999;Grelle, 2003;Marshall et al, 2014;Luna et al, 2017). Gadelha et al (2017), studying a primate community in a habitat similar to that in the current study, found a significant association between mammalian abundance, and absolute dominance of trees, number of clearings, and vegetation height. No studies to date, however, had tested the effects of the forest structure and productivity covariates on whole assemblages of medium-and large-sized mammals in totally protected areas in the Brazilian Amazonia.…”
Section: Introductionmentioning
confidence: 48%
“…It has been shown in our previous studies (Gadelha et al, 2017;Luna et al, 2017) that at the regional scale (Peterson et al, 2011), the abundance of the mammalian assemblages can be determined by the physical structure of forests, whether it be in highly-heterogeneous vegetation mosaics, such as in the northern part of the Guyana Shield, or the ombrophilous forests of the southern part, or a transition between them. Now, we have also shown that at the local scale (Peterson et al, 2011), forest structure and productivity, and more specifically food availability and its fluctuations, determined the abundance of the mammalian assemblages.…”
Section: Discussionmentioning
confidence: 94%